Cell cycle entry, maintenance, and exit during plant development - Polyn, Stefanie; Willems, Alex; De Veylder, Lieven (Current opinion in plant biology, 2015)
•RBR1 stands at the crossroad of cell cycle entry, maintenance, and exit.•TOR1 and CYCP2;1 control the heterotrophic to auxotrophic growth switch.•Cell cycle maintenance is mastered at the stem cell level.•Two classes of CDK-inhibitors play distinct roles at cell cycle exit. Growth and development of plants are driven by the continuous production of new cells at the meristems; hence, it is of pivotal importance for plants to precisely regulate the timing and extent of cell proliferation. Although over the past decades the molecular components underlying cell cycle progression have been the subject of intensive research, knowledge remains scarce on how the various elements connect with developmental pathways. Recently, advances have been made that link cell cycle entry with nutrient availability, cell division maintenance with stem cell organization, and cell cycle exit with reactive oxygen species and developmental programs.